Evidence for Tonic Control by the GABAA Receptor of Extracellular D-Serine Concentrations in the Medial Prefrontal Cortex of Rodents - Umino, Asami; Ishiwata, Sayuri; Iwama, Hisayuki; Nishikawa, Toru (Frontiers in Molecular Neuroscience, 2017)
Endogenous D-serine is a putative dominant co-agonist for the N-methyl-D-aspartate glutamate receptor (NMDAR) in the mammalian forebrain. Although the NMDAR regulates the higher order brain functions by interacting with various neurotransmitter systems, the possible interactions between D-serine and an extra-glutamatergic system largely remain elusive. For the first time, we show in the rat and mouse using an in vivo microdialysis technique that the extracellular D-serine concentrations are under tonic increasing control by a major inhibitory transmitter, GABA, via the GABAA receptor in the medial prefrontal cortex. Thus, an intra-medial prefrontal cortex infusion of a selective GABAA receptor antagonist, bicuculline, caused a concentration-dependent and reversible decrease in the extracellular levels of D-serine in the rat medial prefrontal cortex without affecting those of another intrinsic NMDAR coagonis, glycine, and an NMDAR agonist, glutamate. The decreasing effects of bicucullin were eliminated by co-infusion of a selective GABAA agonist, muscimol, and were mimicked by a GABAA antagonist, gabazine. In contrast, selective blockade of the GABAB or homomeric ρGABAA (formerly GABAC) receptor by saclofen or (1,2,5,6-tetrahydropyridin-4-yl)-methylphosphinic acid, respectively, failed to downregulate the prefrontal extracellular D-serine levels. Moreover, the local bicucullin application attenuated the ability of NMDA given to the medial prefrontal cortex to increase the cortical extracellular concentrations of taurine, indicating the hypofunction of the NMDAR. Finally, in the mouse medial prefrontal cortex, the reduction of the extracellular D-serine levels by a local injection of bicuculline into the prefrontal portion was replicated, and was precluded by inhibition of the neuronal or glial activity by co-local injection with tetrodotoxin or fluorocitrate, respectively. These findings suggest that the GABAA receptor-mediated regulation of the D-serine signaling may exert fine-tuning of the NMDAR function and require both neuronal and glial activities in the mammalian medial prefrontal cortex.